Is job satisfaction enhancing learning-training transfer relationship? - Zumrah, AR (Emerald Group Publishing Ltd, 2024)
Purpose - One important factor that influences the success of transfer of training in the workplace is the employees' learning level following the training. The association between learning and transfer of training has been established by previous studies. However, to date only a few empirical studies have examined the moderating factor that could strengthen the link between these two variables. This study has been conducted to addresses this gap. Specifically, the purpose of this paper is to explore the moderating effect of job satisfaction on the relationship between learning and transfer of training. Design/methodology/approach - The data for this study have been collected from two sources: the employees of public sector organizations in Malaysia and their supervisors through surveys. Findings - The findings reveal that learning has an important role as a predictor of transfer of training but job satisfaction was found to have no moderating effect in this study. Research limitations/implications - The finding illustrate that management in public sector need to ensure that the employee gains new knowledge and skills from a particular training they have attended, in order to maximize return on training investment. Originality/value - This study extends the discussion and understanding on factors that influence transfer of training at public sector organizations in a non-Western context, specifically Malaysia, a developing country in Southeast Asia.